Increased Serum VEGF-B Level Is Associated With Renal Function Impairment in Patients With Type 2 Diabetes - Wei, Yaping; Han, Shiyu; Zhou, Ruonan; Xu, Pingyuan; Zhou, Lingyan; Zhu, Ziwei; Kan, Yue; Yang, Xiaoying; Xiang, Yingying; Cao, Yue; Jin, Yu; Yan, Jing; et al. (Frontiers in Endocrinology, 2022)
Aims/Introduction Renal function impairment related to type 2 diabetes (T2DM) presents serious threat to public health. Previous studies suggest that vascular endothelial growth factor-B (VEGF-B) might contribute to renal injury. Therefore, this study investigated the association of serum VEGF-B level with the risk of renal function impairment in T2DM patients. Materials and Methods Serum VEGF-B levels were measured in 213 patients with type 2 diabetes and 31 healthy participants. Participants with type 2 diabetes were further divided into a group of 112 participants with eGFR<90 mL/min/1.73m2 and 101 participants with eGFR≥ 90 mL/min/1.73m2. Clinical data were collected, and a binary logistic regression model was employed to test the association between potential predictors and eGFR. Results Serum VEGF-B levels evaluated in type 2 diabetes patients compared with healthy controls. In patients with type 2 diabetes, serum VEGF-B level was positively correlated with triglyceride, serum creatinine and cystatin C while negatively correlated with HDL-C and eGFR. Binary logistic regression showed that serum VEGF-B level was an independent risk factor of eGFR<90 mL/min/1.73m2. Conclusions Serum VEGF-B level is associated with renal function impairment in patients with type 2 diabetes and may be a potential drug target for diabetic kidney disease.